Case report: A case report and literature review of complete trisomy 9 - Xu, Chenxia; Li, Miaoyuan; Peng, Jianming; Zhang, Yanfang; Li, Haijun; Zheng, Guobing; Wang, Degang (Frontiers in Genetics, 2023)
Complete trisomy 9 is a rare and lethal chromosomal anomaly characterized by multisystem dysmorphism and central nervous system (CNS) malformations. This study presents a case of complete trisomy 9 with an unusual phenotypic association and investigates the genetic pathways involved in this chromosomal abnormality. Trisomy 9 leads to a wide range of organ abnormalities, and this research contributes to a better understanding of the phenotype associated with this rare aneuploidy. The phenotypes of fetuses with various systems affected by complete trisomy 9 in the literature were reviewed and summarized. Correct diagnosis and appropriate counseling based on the characteristics of previous reports of fetuses with trisomy 9 is essential in maternity care and clinical management. To provide guidance and help for clinical diagnosis this study aimed to explore the clinical and genetic characteristics of trisomy 9 syndrome to improve clinicians’ understanding of the disease.